The Qur'an: Its Orality and Interpretation - Gusmian, Islah; Abdullah, Mustaffa (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
This article sets out the use of orality as an element in the interpretation of the Qur’an. Oralities in the Qur'an, such as rhyme, sound structure, and diction used in the Qur’an, are frequently regarded as part of the Qur’an’s miracles and are hardly linked with Qur’an interpretation. Indeed, the orality component is closely related to the messages found in the Qur’an. This article demonstrates that rhyme and sound structure are essential characteristics employed by the Qur’an to deliver messages through recognizing orality as an indispensable aspect of the Qur’an’s construction. Both can be perceived psychologically by listeners or readers of the Qur’an. Specific dictions in some verses were also employed as a medium to communicate the Qur'an's worldview while rejecting Arab society’s views at the time. Orality has become a prominent feature of Qur’an interpretation.